"It was there when I came home": young adults and jail reentry in the context of COVID-19 - Abrams, Laura S. (American journal of criminal justice, 2023)
In this study, the authors explore how young adults navigated the dual challenges of the COVID-19 pandemic and jail reentry in a large urban environment. Fifteen young adults (aged 18-25) participated in up to nine monthly semi-structured interviews to discuss their experiences of reentry during the height of the COVID-19 pandemic (i.e., spring and summer 2020). Participants held mixed attitudes and beliefs about COVID-19. Several participants viewed the pandemic as a hoax, while others took the pandemic more seriously, particularly if their friends and family members had contracted the virus. Yet nearly all participants viewed the pandemic as having a relatively minimal impact on their lives compared to the weight of their reentry challenges and probation requirements. Young adults described COVID-19 stay-at-home orders as limiting their exposure to negative influences and facilitating compliance with probation requirements. However, resource closures due to COVID-19, including schools, employment programs, and social services presented barriers to reentry success. The authors draw upon these findings to pose implications for interventions supporting young adult reentry.